Developing a protocol on antimicrobial resistance through WHO's pandemic treaty will protect lives in future pandemics - Arne Ruckert; Shajoe Lake; Susan Rogers Van Katwyk (BMC, 2024)
Abstract Addressing antimicrobial resistance (AMR) through the pandemic treaty is a crucial aspect of pandemic prevention, preparedness, and response. At the moment, AMR-related provisions in the draft text do not go far enough and will likely lead countries to commit to the status-quo of AMR action. We suggest that the protocol mechanism of the treaty proposed under Article 31 offers an opportunity to develop a subsidiary agreement (or protocol) to further codify the specific obligations and enforcement mechanisms necessary to meet the treaty's AMR provisions. We also highlight experiences with previous treaty implementation that relied on protocols to inform design of a future AMR protocol.